This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Theoretical Dynamics September 24, 2010 Homework 3 Instructor: Dr. Thomas Cohen Submitted by: Vivek Saxena 1 Goldstein 8.1 1.1 Part (a) The Hamiltonian is given by H ( q i ,p i ,t ) = p i q i L ( q i , q i ,t ) (1) where all the q i s on the RHS are to be expressed in terms of q i , p i and t . Now, dH = H q i dq i + H p i dp i + H t dt (2) From (1), dH = p i d q i + q i dp i dL = p i d q i + q i dp i L q i dq i + L q i d q i + L t dt = L q i dq i + q i dp i + p i L q i d q i L t dt (3) Comparing (2) and (3) we get H q i = L q i = p i (2nd equality from Hamiltons equation) (4) q i = H q i (also Hamiltons equation) (5) p i L q i = 0 (H is not explicitly dependent on q i ) (6) L t = H t (7) From (4) and (6) we have d dt L q i L q i = 0 , i = 1 , 2 ,...,n (8) which are the EulerLagrange equations. 3 1 1.2 Part (b) L ( p, p,t ) = p i q i H ( q,p,t ) (9) = p i q i H ( q,p,t ) d dt ( p i q i ) (10) = L ( q, q,t ) d dt ( p i q i ) (11) = L ( q, q,t ) p i q i p i q i (12) So, dL = L p i dp i + L p i d p i + L t dt (13) = q i dp i q i d p i + L t dt (from (9)) (14) Comparing (12) and (13) we get q i = L p i (15) q i = L p i (16) Thus the equations of motion are d dt L p i L p i = 0 , i = 1 , 2 ,...,n (17) 2 Goldstein 8.6 Hamiltons principle is Z Ldt = 0 (18) or equivalently Z 2 Ldt = 0 (19) We can subtract the total time derivative of a function whose variation vanishes at the end points of the path, from the integrand, without invalidating the variational principle. This is because such a function will only contribute to boundary terms involving the variation of q i and p i at the end points of the path, which vanish by assumption. Such a function is p i q i . So, the modified Hamiltons principle is Z 2 L d dt ( p i q i ) dt = 0 (20) 3 2 Using the Legendre transformation, this becomes Z (2 p i q i 2 H p i q i p i q i ) dt = 0 (21) = Z (2 H + p i q i p i q i ) dt = 0 (22) now, p i q i p i q i = q 1 ... q n  p 1 ... p n 1 2 n n n 1 n n 1 n n n n 2 n 2 n q 1 . . q n p 1 . . p n 2 n 1 (23) = T J (24) So (22) becomes Z ( 2 H + T J ) dt = 0 (25) which is the required form of Hamiltons principle. 3 Goldstein 8.9 The constraints can be incorporated into the Lagrangian L by defining a constrained Lagrangian L c , as L c ( q, q,t ) = L ( q, q,t ) X k k k ( q,p,t ) (26) Applying Hamiltons principle, and using the Legendre transformation for L , we get Z p i q i H ( q,p,t ) X k k k ( q,p,t ) !...
View
Full
Document
This note was uploaded on 12/29/2011 for the course PHYSICS 601 taught by Professor Hassam during the Fall '11 term at Maryland.
 Fall '11
 Hassam
 mechanics, Work

Click to edit the document details